2004
DOI: 10.1517/14622416.5.7.895
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in eleven phase I drug metabolism genes in an ethnically diverse population

Abstract: The extent of genetic variation found in drug metabolism genes and its contribution to interindividual variation in response to medication remains incompletely understood. To better determine the identity and frequency of variation in 11 phase I drug metabolism genes, the exons and flanking intronic regions of the cytochrome P450 (CYP) isoenzyme genes CYP1A1, CYP1A2, CYP2A6, CYP2B6, CYP2C8, CYP2C9, CYP2C19, CYP2D6, CYP2E1, CYP3A4 and CYP3A5 were amplified from genomic DNA and sequenced. A total of 60 kb of bi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
125
1
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(135 citation statements)
references
References 43 publications
5
125
1
4
Order By: Relevance
“…Individuals who have normal metabolic activity are called extensive metabolizers (EM) whereas individuals with defective metabolic activity are called poor metabolizers (PM;Meyer 1990). It has been reported that phenotypes associated with genetic variations often contribute to differences in drug metabolism and the dynamics of drug-drug interactions (Solus et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Individuals who have normal metabolic activity are called extensive metabolizers (EM) whereas individuals with defective metabolic activity are called poor metabolizers (PM;Meyer 1990). It has been reported that phenotypes associated with genetic variations often contribute to differences in drug metabolism and the dynamics of drug-drug interactions (Solus et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic polymorphisms have been reported to have variable frequency in different ethnic populations 13,14) . The pharmacogenetics of enzymes participating in drug metabolism is responsible for a significant portion of drug-induced toxicity as polymorphisms in these genes contribute to alterations in drug clearance and influence the efficacy and toxicity of drug therapy 15) .…”
Section: Discussionmentioning
confidence: 99%
“…As CR comprises both parameters of "no vomiting" and "no rescue medication use", this may have contributed to the equivocal CR rates between arms. Since aprepitant is both a substrate and moderate inhibitor of CYP3A4 [29,30], genetic differences [29,31] may have accounted for the varying aprepitant efficacies between this study, which comprised of 100% ethnic Chinese patients, and similar studies which sampled a large proportion of Caucasians [22].…”
Section: Implications To Cinv Controlmentioning
confidence: 93%